A Comparative Study of Writing Proficiency in Korean Heritage and Non-Heritage Learners: Linguistic Characteristics and Pedagogical Insights - Inho Jung (Journal of the National Council of Less Commonly Taught Languages)
This study examines the linguistic characteristics of Korean Heritage Language (KHL) learners compared to Non-Heritage Language (NHL) learners through corpus analysis, Error Analysis (EA), and t-tests. Findings reveal that KHL learners produce longer sentences, demonstrate higher lexical diversity, and make fewer morphological and syntactic errors, though they are more prone to orthographic errors from phonemic transfer. NHL learners, in contrast, struggle more with morphology and syntax but show fewer orthographic errors. T-tests on lexical metrics showed no significant differences between groups, suggesting similar written output, while t-tests on error types revealed a significant difference in morphological errors, with NHL learners making more mistakes. The study emphasizes targeted instruction, recommending orthographic support for KHL learners and morphological and syntactic assistance for NHL learners. Collaborative learning between the groups is proposed to leverage their strengths. Despite a small dataset, this research contributes to understanding heritage language learning and informs tailored pedagogical strategies.